Preparedness of nurses to work in neonatal intensive care unit in a selected tertiary care facility: An observational study - Joshi, Poonam; Paul, Jessy Shaji; Surya, Sonali; Thukral, Anu; Deorari, Ashok K (Indian Journal of Child Health, 2018)
Background: Neonates admitted in neonatal intensive care units (NICUs) require specialized neonatal nursing care. Objective: The objective of this study was to generate evidence on quality of neonatal nursing by assessing the preparedness of nurses in terms of knowledge and skills in neonatal nursing at pre-service level with respect to specific neonatal procedures and to further explore their self-perception about performing these procedures. Materials and Methods: In this cross-sectional observational study, 36 out of 600 newly joined nurses were randomly recruited. A pre-validated tool consisting of structured knowledge questionnaire, observation checklists for objectively structured clinical examination stations, and self-preparedness scale was used. The knowledge and skill scores were graded as excellent (>80%), average (60–80%), and poor (<60%). Results: A total of 36 nurses (age median, interquartile range; 24 [23–29]) participated in the study. The basic qualification of majority of subjects (30, 83.4%) was BSc nursing. The median duration of didactic classroom learning (h) and clinical posting (weeks) in neonatology was 15 (3–45) and 1.5 (0.3–4), respectively. One-third of the subjects (12, 33.3%) did not have any clinical posting in NICU at pre-service level. The mean knowledge, skill, and self-preparedness scores of nurses along with the range were 11.8 ± 2.1 (8–16), 56.9 ± 7.2 (42–72), and 60.0 ± 13.4 (26–80), respectively. More than 60% of nurses had excellent knowledge scores (>80%); similar number had poor overall skills (<60%). Skills of the more than half of nursing personnel were average in hand hygiene (58.3%), temperature recording (52.8%), and prevention of hypothermia (52.8%) while poor in weight recording (75%), bag and mask ventilation (69.4%), intravenous drug administration (63.9%), and orogastric feeding (58.3%). No correlation was found among knowledge, skill, and preparedness scores (p>0.05). The median self-preparedness scores of the nurses suggested their overestimation regarding performing the neonatal procedures. Conclusion: Preparedness of the nurses to work in NICU in terms of skills to perform various neonatal procedures was inadequate and hence requires attention.